2009
DOI: 10.1111/j.1439-0531.2007.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Body Condition Change Ante‐ and Postpartum, Health and Reproductive Performance in German Holstein Cows

Abstract: The effects of body condition score (BCS) change and status ante- and postpartum (pp) on health and reproductive performance in 234 German Holstein cows from eight dairy farms were evaluated. BCS was determined from 6 weeks antepartum until 20 weeks pp in 2-week intervals. Three and 5 weeks pp progesterone concentrations in blood serum were determined to detect the presence of luteal tissue as an indicator of cyclicity. The incidence of various diseases, percent cycling cows, reproductive measures and culling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
83
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 19 publications
16
83
2
3
Order By: Relevance
“…Older cows are generally at higher risk (Espejo et al, 2006;Bicalho et al, 2007b;Dippel et al, 2009), and incidence of lameness peaks 3 to 4 mo into lactation (Green et al, 2002). Thinner digital cushion (Bicalho et al, 2009), higher milk production at the beginning of lactation (Green et al, 2002;Bicalho et al, 2008), and low BCS (<3.0) before and at calving (Hoedemaker et al, 2009) were identified as cow-level risk factors for lameness. found that cows that became lame spent more time standing with only 2 front feet in the stall compared with cows that did not become lame (6.2% vs. 5.6% of the day, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Older cows are generally at higher risk (Espejo et al, 2006;Bicalho et al, 2007b;Dippel et al, 2009), and incidence of lameness peaks 3 to 4 mo into lactation (Green et al, 2002). Thinner digital cushion (Bicalho et al, 2009), higher milk production at the beginning of lactation (Green et al, 2002;Bicalho et al, 2008), and low BCS (<3.0) before and at calving (Hoedemaker et al, 2009) were identified as cow-level risk factors for lameness. found that cows that became lame spent more time standing with only 2 front feet in the stall compared with cows that did not become lame (6.2% vs. 5.6% of the day, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Some conditions such as high milk production in early lactation (Bicalho et al, 2008), low body condition score during the periparturient period (Hoedemaker et al, 2009), age (Dippel et al, 2009), and environment as type of flooring, presence of dirt, and humidity (Cook and Nordlund, 2009) may enhance the occurrence of lameness in the herd. Lesions in the limbs can result in lower milk production (Bicalho et al, 2008), reduced fertility, and increased risk of premature culling (Bicalho et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Η αρνητική επίδραση της μείωσης του Δ.Θ.Κ. κατά τη διάρκεια της ξηράς περιόδου στην αναπαραγωγική ικανότητα των αγε λάδων αναδεικνύεται και στην πρόσφατη μελέτη των Hoedemaker et al (2008).…”
Section: επιδραση Toy δθκ στην αναπαραγωγικη ικανοτητα των γαλακτοunclassified